Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1167/iovs.12-9724
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Alpha Linolenic Acid on Human Corneal Epithelial Cells

Abstract: ALA may serve as a potent anti-inflammatory agent in ocular surface inflammation. The anti-inflammatory effects of ALA are comparable to those of corticosteroids, and are mediated through NF-κB signal transduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 39 publications
2
61
0
3
Order By: Relevance
“…91 IL-8 is also an important inflammatory mediator during infection, 92 and is increased in corneal epithelial cells in response to lipopolysaccharide stimulation. 93 Santacruz et al reported that IL-1β, IL-6 and IL-8 were elevated in tears from eyes with infectious keratitis, compared with those in the control contralateral eyes. 94 …”
Section: Bilateral Alteration In Tear Cytokinesmentioning
confidence: 98%
“…91 IL-8 is also an important inflammatory mediator during infection, 92 and is increased in corneal epithelial cells in response to lipopolysaccharide stimulation. 93 Santacruz et al reported that IL-1β, IL-6 and IL-8 were elevated in tears from eyes with infectious keratitis, compared with those in the control contralateral eyes. 94 …”
Section: Bilateral Alteration In Tear Cytokinesmentioning
confidence: 98%
“…Nutritionally, C20:5 eicosapentaenoic acid (EPA) and C22:6 docohexaenoic acid (DHA) are the most important VLC-PUFAs belonging to the v-3 family. Out of the v-6 family, C18:1 alfa linoleic acid (ALA) [2] and C20:4 arachidonic acid (AA) [3] have also been shown to have health benefits. There is a considerable amount of research that supports the beneficial health properties of VLC-PUFAs, particularly the v-3 FAs [4].…”
Section: Introductionmentioning
confidence: 99%
“…Rashid et al’s study has shown that the topical administration of omega-3 fatty acid in DES mouse model decreased the number of CD11b + cells and the levels of pro-inflammatory cytokines such as IL-1α and TNF-α in the ocular surface. 7 Recently, a study we have conducted had shown that administration of Alpha linolenic acid (ALA) to HCE cells stimulated by Lipopolysaccharide (LPS) or polyriboinosinic:polyribocytidylic acids (poly I:C) in-vitro significantly reduced the protein and mRNA levels of several pro-inflammatory cytokines [13]. …”
Section: Discussionmentioning
confidence: 99%
“…Both protein and mRNA levels of several pro-inflammatory cytokines were dramatically decreased following treatment with ALA [13]. The results of that study have paved the way for further search of PUFAs bioactive derivatives, which may have a stronger anti-inflammatory effect.…”
Section: Introductionmentioning
confidence: 99%